The Effect of Time to Castration Resistance on Overall Survival and Success of Docetaxel Treatment in Castration Resistant Prostate Cancer Patients - Suer, Evren; Hamidi, Nurullah; Akpinar, Cagri; Gokce, Mehmet Ilker; Gulpinar, Omer; Turkolmez, Kadir; Beduk, Yasar; Baltaci, Sumer (Urology Journal, 2019)
Purpose: To investigate the prognostic role of time to castration resistance(TTCR) in patients who have received solely Docetaxel chemotherapy regimen(DCR) for castration resistant prostate cancer(CRPC). Methods: Between Jan 2004 and Dec 2015, data of 162 patients who have received DCR for CRPC were gathered. Patients were divided into three groups according to TTCR: Group 1(? 12 months), group 2(13-24 months), and group 3(>24 months). Data of age, clinical stage, Gleason grade(GG), previous treatments, site of metastases, Prostate-specific antigen (PSA) values, TTCR, overall survival, biochemical progression free survival(PFS) and PSA response to docetaxel were recorded. Result: The mean age of the 162 patients was 74.4 ± 8.5 years. Data on mean age, type of castration, adding estramustine to docetaxel, secondary hormonal manipulation, Gleason grade, clinical T stage at initial diagnosis and site of metastases were comparable between three groups. PSA values were higher in group 1 than other groups. PSA response to docetaxel was 59.2% in all patient and it was worse in group 1 than other groups (P = .009). Two years overall survival rates were 7.6%, 25% and 32.3% in group 1, 2 and 3, respectively. Median survival rates were 7, 14 and 23 months in group 1, 2 and 3, respectively, and this difference was statistically significant (P=.016). On multivariate analysis, TTCR was found to be independent prognostic factor for overall survival and response to docetaxel treatment. Conclusion: TTCR appears to be an independent prognostic factor for patients who are candidates for DCR.